Upaya Pemberdayaan Subak Umabun sebagai Lembaga Agribisnis di Desa Angantaka Kecamatan Abiansemal Kabupaten Badung - DEWA PUTU ALIT SUDIRA; NI WAYAN SRI ASTITI; I GEDE SETIAWAN ADI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Measuring Empowerment Subak Umabun As Agribusiness Board at VillageAngantaka Abiansemal Badung District Research efforts empowerment subak as agribusiness board aims to boost the economyand the welfare of farmers, so that the culture of agriculture demand and not abandonedby society, particularly Subak Umabun. This study aims to (1) identify the potentialSubak Umabun related to natural resources, human resources and financial resources,(2) To know the efforts made to empower the board to Subak Umabun agribusiness.This research was conducted at Subak Umabun, the number of respondents 75 peopleappointed by the formula slovin, data that is used structured interviews and in-depthinterviews.The results showed that the potential of Subak Umabun aspects of naturalresources, human resources and financial resources are classified with an average scoreof 3,19. Further empowerment undertaken by Subak Umabun are classified by score of3,21. And the last institution in agribusiness Subak Umabun high achievement score of3,68. Based on these results, it is recommended to the government through theDepartment of Agriculture, Plantation and Forestry Badung need to deepen the study ofthis kind, so that the programs formulated by the government not only in the form ofsocial assistance